2012
DOI: 10.1177/1071181312561063
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Role of Cognition in Cyber Security

Abstract: The cyber security task is an intensely cognitive task that is embedded in a large multi-layered sociotechnical system of analysts, computers, and networks. Effective performance in this world is hampered by enormous size and complexity of the network data, the adaptive nature of intelligent adversaries, the lack of ground truth to assess performance, the high number of false alarms presented by automated alerting systems, by organizational stove pipes thwarting collaboration, and by technology that is thrown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…While we found little data on the cognitive process of individual clinicians, we found substantial data on how teams with different expertise and experience levels can effectively work together to identify, mitigate and escalate the recognition of patient risk. Our subthemes of shared language and training and structure to support handoffs and continuity of care demonstrate the importance of shared SA in the inpatient setting 3 11. Shared SA requirements are dependent on the scenario, goals and tasks at hand.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While we found little data on the cognitive process of individual clinicians, we found substantial data on how teams with different expertise and experience levels can effectively work together to identify, mitigate and escalate the recognition of patient risk. Our subthemes of shared language and training and structure to support handoffs and continuity of care demonstrate the importance of shared SA in the inpatient setting 3 11. Shared SA requirements are dependent on the scenario, goals and tasks at hand.…”
Section: Discussionmentioning
confidence: 96%
“…Concepts of SA have been extended to address individual SA, team SA, shared SA and distributed SA (box 1). 3 7 11
Definitions for and examples of related types of situation awareness (SA) Individual SA : An individual's perception of data elements, the comprehension of their meaning in context and the projection of their status in the near future. Example: A physician determines that fever, tachycardia and symptoms of acute respiratory distress syndrome are due to severe sepsis with a high risk of rapid deterioration.
…”
Section: Background and Significancementioning
confidence: 99%
“…Some studies have dealt with cybersecurity through analyzing situational awareness which includes cognitive studies [22,23,24,25] while some others have studied behavioral aspects to understand general cybersecurity awareness in organizations [26,27,28]. In this paper, we also aimed to understand the antecedents and consequents of general cybersecurity awareness among maritime employees, which are shown in Figure 1 and Table 1.…”
Section: Antecedentsmentioning
confidence: 99%
“…Intraorganization diffusion of strategies is central to an effective defense against attacks (Cooper & Wolfe, 2005). Cognitive task analysis and qualitative interviews (Champion, Rajivan, Cooke, & Jariwala, 2012;McNeese, et al, 2012) have revealed a lack of support for the major issues of splintered communication and lack of team collaboration among cyber defense teams.…”
Section: Expanding Current Modelsmentioning
confidence: 99%